"Even though we're married, I'm single": the meaning of jail incarceration in romantic relationships - Turney, Kristin (Criminology, 2023)
Jail incarceration substantially transforms romantic relationships, and incarceration may alter the commitment between partners, thereby undermining or strengthening relationships. In this article, we use in-depth interviews with 85 women connected to incarcerated men (as current or former romantic partners) to explore how women articulate relationship changes that stem from their partner's jail incarceration, a common but understudied form of contact with the criminal legal system. We identify three interrelated and mutually reinforcing processes, which are shaped by and shape a partner's commitment to the relationship. First, incarceration produces liminality in the status of the relationship. Second, incarceration fosters women's sense of independence from their incarcerated partners. Third, incarceration creates space for partners to reevaluate how they prioritize the relationship in their lives. Jail incarceration intervenes in romantic relationships at different points during each relationship, and accordingly, women experience heterogeneity in processes of liminality, independence, and reprioritization. These processes contribute to differential relationship experiences, with some relationships deteriorating during incarceration, others strengthening, and others neither deteriorating nor strengthening. By systematically uncovering these processes linking jail incarceration to romantic relationships, we advance an understanding of how the criminal legal system can shape relationship commitment processes and inequalities among families.